An Acute Bout of Soccer Heading Subtly Alters Neurovascular Coupling Metrics - Smirl, Jonathan D.; Peacock, Dakota; Wright, Alexander D.; Bouliane, Kevin J.; Dierijck, Jill; Burma, Joel S.; Kennefick, Michael; Wallace, Colin; van Donkelaar, Paul (Frontiers in Neurology, 2020)
Objective: The current investigation examined how a bout of soccer heading may impact brain function. Design: Semi-randomized crossover cohort. Setting: Controlled soccer heading. Participants: Seven male soccer players (24.1 ± 1.5 years). Intervention: 40 successful soccer headers were performed in 20 minutes (25m, launch velocity ~80 km/hr). X2 xPatch recorded linear and rotational head accelerations during each impact. A contact control ‘sham’ condition – ball made body contact, but not by the head; and a no activity time ‘control’ condition were also completed. Main Outcome Measures: Posterior and middle cerebral artery (PCA and MCA, respectively) cerebral blood velocity (CBV) was recorded during a visual task (neurovascular coupling: NVC) alongside SCAT3 symptoms scores pre/post a controlled bout of soccer heading. Results: Cumulative linear and rotational accelerations were 1,57497.9 g and 313,761±23,966 rads/s2, respectively during heading and changes in SCAT3 symptom number (pre: 2.6±3.0; post: 6.7±6.2, p=0.13) and severity (pre: 3.7±3.6, post: 9.4±7.6, p=0.11) were unchanged. In the PCA, no NVC differences were observed, including: relative CBV increase (28.0±7.6%, p=0.71) and total activation (188.7±68.1 cm, p=0.93). However, MCA-derived NVC metrics were blunted following heading, demonstrating decreased relative CBV increase (7.8±3.1 %, p=0.03) and decreased total activation (26.7±45.3 cm, p=0.04). Conclusion: Although an acute bout of soccer heading did not result in an increase of concussion-like symptoms, there were alterations in NVC responses within the MCA during a visual task. This suggests an acute bout of repetitive soccer heading can alter CBV regulation within the region of the brain associated with the header impacts.